Did you mean

2x

(2x - 5)(x + 4) = 0

2x - 5 = 0 x + 4 = 0

2x = 5 x = -4

x = 5/2

x = 5/2 & -4

2x

^{2}+ 3x - 20 = 0(2x - 5)(x + 4) = 0

2x - 5 = 0 x + 4 = 0

2x = 5 x = -4

x = 5/2

x = 5/2 & -4

2x

(2x - 5)(x + 4) = 0

2x - 5 = 0 x + 4 = 0

2x = 5 x = -4

x = 5/2

x = 5/2 & -4

2*2 + 3x - 20 = 0

4 + 3x - 20 = 0

3x - 20 = -4

3x = 16

x = 5-1/3

Proof:

4 + 3 (5-1/3) - 20 = 0

4 + (16) - 20 = 0

20 - 20 = 0

4 + 3x - 20 = 0

3x - 20 = -4

3x = 16

x = 5-1/3

Proof:

4 + 3 (5-1/3) - 20 = 0

4 + (16) - 20 = 0

20 - 20 = 0

Didn't find the answer you were looking for?